Changes of the in vivo kinematics of the human medial longitudinal foot arch, first metatarsophalangeal joint, and the length of plantar fascia in different running patterns - Sun, Xiaole; Su, Wanyan; Zhang, Faning; Ye, Dongqiang; Wang, Shaobai; Zhang, Shen; Fu, Weijie (Frontiers in Bioengineering and Biotechnology, 2022)
Accurately obtaining the in vivo motion of the medial longitudinal arch (MLA), first metatarsophalangeal joint (MTPJ), and plantar fascia (PF) is essential for analyzing the biomechanics of these structures in different running strike patterns. Most previous studies on the biomechanics of the MLA, first MTPJ, and PF have been based on traditional skin-marker–based motion capture, which cannot acquire the natural foot motion. Therefore, this study aimed to 1) describe the movement of the MLA, first MTPJ, and PF during running by using the high-speed dual fluoroscopic imaging system (DFIS) and 2) explore changes of the in vivo kinematics of the MLA and first MTPJ, and the length of the PF during the stance phase of running with different foot strike patterns. Fifteen healthy male runners all of whom ran with a regular rearfoot strike (RFS) pattern were required to run with forefoot strike (FFS) and RFS patterns. Computed tomography scans were taken from each participant’s right foot for the construction of 3D models (the calcaneus, first metatarsal, and first proximal phalanges) and local coordinate systems. A high-speed DFIS (100 Hz) and 3D force platform (2,000 Hz) were used to acquire X-ray images of the foot bones and ground reaction force data during the stance phase of running (3 m/s ± 5%) simultaneously. Then, 3D-2D registration was used to obtain the in vivo kinematic data of the MLA and first MTPJ and the length of the PF. When compared with RFS, in FFS, 1) the range of motion (ROM) of the medial/lateral (5.84 ± 5.61 mm vs. 0.75 ± 3.38 mm, p = 0.002), anterior/posterior (14.64 ± 4.33 mm vs. 11.18 ± 3.56 mm, p = 0.010), plantarflexion/dorsiflexion (7.13 ± 3.22° vs. 1.63 ± 3.29°, p < 0.001), and adduction/abduction (−3.89 ± 3.85° vs. −0.64 ± 4.39°, p = 0.034) motions of the MLA were increased significantly; 2) the ROM of the anterior/posterior (7.81 ± 2.84 mm vs. 6.24 ± 3.43 mm, p = 0.003), superior/inferior (2.11 ± 2.06 mm vs. −0.57 ± 1.65 mm, p = 0.001), and extension/flexion (−9.68 ± 9.16° vs. −5.72 ± 7.33°, p = 0.018) motions of the first MTPJ were increased significantly; 3) the maximum strain (0.093 ± 0.023 vs. 0.075 ± 0.020, p < 0.001) and the maximum power (4.36 ± 1.51 W/kg vs. 3.06 ± 1.39 W/kg, p < 0.001) of the PF were increased significantly. Running with FFS may increase deformation, energy storage, and release of the MLA and PF, as well as the push-off effect of the MTPJ. Meanwhile, the maximum extension angle of the first MTPJ and MLA deformation increased in FFS, which showed that the PF experienced more stretch and potentially indicated that FFS enhanced the PF mechanical responses.